2011
DOI: 10.1589/jpts.23.553
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Isometric Muscle Strength Measurements of the Lower Limbs Using a Hand-held Dynamometer and Belt: a Comparison with an Isokinetic Dynamometer

Abstract: Abstract.[Purpose] The aim of this study was to evaluate the validity of isometric muscle strength measurements of the lower limbs and hips made with a hand-held dynamometer and belt by comparing them with measurements obtained by an isokinetic dynamometer.[Subjects] The subjects were 24 healthy adults (12 men, 12 women) with a mean age of 20.4 years.[Method] Measurements were made with both instruments on the flexors, extensors, abductors, adductors, external rotators and internal rotators of the hip and flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 20 publications
4
53
4
Order By: Relevance
“…Direct comparison of the HHD results from this study with others can be seen in Table 3. Both Weng et al [3] (Nm/Kg) and Katoh et al [4] (N) reported isometric strength differently to us (Nm/m). Whilst both used healthy subjects Katoh et al [15] did not report the participants as athletic and this could explain the higher scores in this study.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Direct comparison of the HHD results from this study with others can be seen in Table 3. Both Weng et al [3] (Nm/Kg) and Katoh et al [4] (N) reported isometric strength differently to us (Nm/m). Whilst both used healthy subjects Katoh et al [15] did not report the participants as athletic and this could explain the higher scores in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…Both Weng et al [3] and Katoh et al [4] found higher scores in the isokinetic method and speculated that this may because of the increased stabilisation that an isokinetic chair provides but also concluded that the HHD isometric method showed moderate to high correlations and could be considered a valid measure of strength. This is supported in a literature review of hip and knee muscle function testing by Maffiuletti [20] who concluded that it may even be preferable because of its relative simplicity and reliability.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In general, an isokinetic dynamometer (IKD) is used to study the validity of knee extension muscle strength measurement. The correlation coefficients between the HHD and IKD have been reported to be 0.918 ) , 0.719 ) , and 0.8610 ) . Nevertheless, differences in the measurement methods have been shown to affect HHD measurement during the sitting position, with lower values than that obtained by IKD measurement9, 10 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The isokinetic dynamometer is the gold standard for muscle strength assessment, but it is extremely expensive [1]. The hand held dynamometer (HHD) is a portable option with validity and reliability comparable to isokinetic dynamometry when assessing isometric muscle strength in several joint movements [1,13,14]. It is important to note the equipment's anchoring method when the strength test is performed using an HHD in order to maintain the validity and reliability [15].…”
Section: Introductionmentioning
confidence: 99%